The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00429-021-02374-w
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two gradients: differences between the left and right hemispheres predict semantic cognition

Abstract: Decomposition of whole-brain functional connectivity patterns reveals a principal gradient that captures the separation of sensorimotor cortex from heteromodal regions in the default mode network (DMN). Functional homotopy is strongest in sensorimotor areas, and weakest in heteromodal cortices, suggesting there may be differences between the left and right hemispheres (LH/RH) in the principal gradient, especially towards its apex. This study characterised hemispheric differences in the position of large-scale … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 135 publications
(249 reference statements)
3
44
0
Order By: Relevance
“…A recent study that applied DME to RS-fMRI data presented evidence for hemispheric asymmetry in semantic networks, which correlated with semantic task performance 93 . The large dataset in that study and the availability of data from both hemispheres in every participant likely facilitated detection of those differences.…”
Section: Hemispheric Lateralizationmentioning
confidence: 99%
“…A recent study that applied DME to RS-fMRI data presented evidence for hemispheric asymmetry in semantic networks, which correlated with semantic task performance 93 . The large dataset in that study and the availability of data from both hemispheres in every participant likely facilitated detection of those differences.…”
Section: Hemispheric Lateralizationmentioning
confidence: 99%
“…Consequently, these regions are placed at different positions along the cortical hierarchy, providing novel insights concerning the system-level variations in the asymmetric brain. Indeed, recent research suggests that the principal gradient is asymmetric ( Liang et al, 2021 ; Gonzalez Alam et al, 2022 ) and that the degree of asymmetry relates to individual differences in semantic performance and visual reasoning ( Gonzalez Alam et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies show that bilateral activation underlies executive function (Camilleri et al, 2018;Fedorenko et al, 2013) and (especially in visual-spatial tasks), the most robust responses are often right-lateralised (Dick et al, 2019;Gonzalez Alam et al, 2018). A recent study found that control networks show different patterns of connectivity across the hemispheres, with left-lateralised control regions showing stronger connectivity with heteromodal regions of the default mode network (Gonzalez Alam et al, 2021). In this way, the left lateralised nature of the semantic control network revealed by our analysis may be adaptive, allowing control regions to separate from visual-spatial responses when internal aspects of cognition are constrained.…”
Section: Discussionmentioning
confidence: 99%
“…While the SCN is largely left-lateralised, the MDN comprises distributed bilateral regions (Camilleri et al, 2018;Gao et al, 2021;Gonzalez Alam et al, 2019). As such, effective semantic control should involve connectivity within the lefthemisphere, while domain-general control should rely more on interhemispheric connectivity (Gonzalez Alam et al, 2021), allowing the integration of information across right-hemisphere regions dominant in the control of visuospatial processing with contralateral frontal regions (Wu et al, 2016). As a result, structural or functional disconnection-symptom mapping may separate semantic control impairment from general executive deficits in a way that cannot be achieved by lesion-symptom mapping in patients with left-hemisphere stroke.…”
Section: Introductionmentioning
confidence: 99%